2023
DOI: 10.3390/biomedicines11123105
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 Infection during Pregnancy Increase the Appearance of Congenital Gastrointestinal Malformations in Neonates?

Timea Elisabeta Brandibur,
Nilima Rajpal Kundnani,
Marioara Boia
et al.

Abstract: Background: COVID-19 was an infection that was capable of bringing the entire world to a standstill position within a period of days to months. Despite the advancements in the medical sector, the contagion was difficult to control and costed the lives of millions of people worldwide. Many short- and long-term effects are witnessed even to date in people that contracted the disease. Pregnant females had to suffer not only the devastating effects of the virus, but also the psycho-social impact of the lockdown. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(76 reference statements)
1
1
0
Order By: Relevance
“…Nevertheless, Rodriguez-Wallberg et al warned of a 44% increase in the rate of miscarriage rate in recent years [ 24 ]. Similar results were also identified by Brandibur et al, who reported that SARS-CoV-2 acute infection during pregnancy was unlikely to cause congenital digestive malformations; however, these authors observed that the number of gastrointestinal malformations was higher during 2022 (n = 47) than during the 3 years (2017–2020) prior to the COVID-19 outbreak (n = 39) [ 26 ].…”
supporting
confidence: 85%
“…Nevertheless, Rodriguez-Wallberg et al warned of a 44% increase in the rate of miscarriage rate in recent years [ 24 ]. Similar results were also identified by Brandibur et al, who reported that SARS-CoV-2 acute infection during pregnancy was unlikely to cause congenital digestive malformations; however, these authors observed that the number of gastrointestinal malformations was higher during 2022 (n = 47) than during the 3 years (2017–2020) prior to the COVID-19 outbreak (n = 39) [ 26 ].…”
supporting
confidence: 85%
“…The effect of the hypercoagulable state known to result from maternal COVID-19 infection was considered by Repucci et al as a possible cause for congenital anomalies secondary to in utero vascular accidents and found not to be associated with GI or limb anomalies in their relatively small single center American cohort [34]. Additionally, increases in microcephaly noted in the late pandemic period in a Canadian cohort was concluded to be more likely secondary to an artifact of enhanced surveillance for anomalies [35], and no conclusion could be made as to increases in GI anomalies due to overall low incidence in a Romanian cohort [36].…”
Section: Discussionmentioning
confidence: 99%